2003
DOI: 10.1016/s0002-9440(10)63518-3
|View full text |Cite
|
Sign up to set email alerts
|

Subicular Dendritic Arborization in Alzheimer's Disease Correlates with Neurofibrillary Tangle Density

Abstract: Intracellular accumulation of PHFtau in Alzheimer's disease (AD) disrupts the neuronal cytoskeleton and other neuronal machinery and contributes to axonal and dendritic degeneration, and neuronal death. Furthermore, amyloid-beta (Abeta) has been reported to be toxic to neurons and neurites. While loss of presynaptic elements is an established feature of AD, the nature and extent of dendritic degeneration has been infrequently studied. We investigated MAP2-immunoreactive dendrites using a novel method of high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 24 publications
(31 reference statements)
2
43
0
2
Order By: Relevance
“…In AD, Ͼ90% of cortical tau aggregation localizes to neuropil threads and dystrophic neurites associated with neuritic plaques, indicating that most tau aggregation occurs in specialized processes rather than in cell bodies (73). These aggregates may affect end points other than viability that are nonetheless important for disease progression, including retraction and loss of dendritic arbors (74) and synaptic contacts (75). For example, intracellular aggregates formed from polyglutamine repeats can inhibit processes especially important for neuronal homeostasis such as axoplasmic flow (76).…”
Section: Discussionmentioning
confidence: 99%
“…In AD, Ͼ90% of cortical tau aggregation localizes to neuropil threads and dystrophic neurites associated with neuritic plaques, indicating that most tau aggregation occurs in specialized processes rather than in cell bodies (73). These aggregates may affect end points other than viability that are nonetheless important for disease progression, including retraction and loss of dendritic arbors (74) and synaptic contacts (75). For example, intracellular aggregates formed from polyglutamine repeats can inhibit processes especially important for neuronal homeostasis such as axoplasmic flow (76).…”
Section: Discussionmentioning
confidence: 99%
“…Several putative indices of neural reserve are also being quantifi ed in 20-m sections from the same brain regions, including neu-rons with cresyl violet stain for Nissl substances, and M13, a mouse monoclonal antibody that identifi es all isoforms of MAP2 for dendrites [72] . Finally, synaptic proteins, including synaptophysin, VAMP, SNAP-25, syntaxin and CDCrel-1, are identifi ed by ELISA [73] .…”
Section: Postmortem Indicesmentioning
confidence: 99%
“…Abnormal neuronal activity in such patients might cause local disruption to ion homeostasis in the brain. Also, recent studies on Alzheimer's disease have shown that dendritic arborization would be affected by the presence of neurofibrillary tangles (Falke et al 2003), bringing about an early abnormality in the tissue myelination (Desai et al 2009). These changes in myelin distribution can be detected through analysis of the conductivity profile, either invasively in laboratory animals (e.g., using our methodology) or in practical situations at a clinic in humans, using impedance tomography (Cheney et al 1999).…”
Section: Future Directionsmentioning
confidence: 99%